Prediction of the onset of detectable multiple site damage in a RAF VC10 circumferential butt joint using extended fatigue specimen testing of retired fuselage structure - Ralph, Steven (Cranfield University, 2004)
The in-flight pressure fuselage failure of an Aloha Airlines Boeing 737 near Maui, Hawaii on 28 April 1988 brought the issue of Ageing Aircraft and in particular the dramatic destructive potential of Widespread Fatigue Damage (WFD) and Multiple Site Damage (MSD) to the attention of the World. The accident led to a substantial amount of research and development work into the WFD phenomenon and civil regulators mandating WFD assessments of ageing aircraft. Although military aircraft are not regulated by civil requirements, military airworthiness requirements require the completion of Ageing Aircraft Audits (AAA), which do require an evaluation of the potential of WFD. This Thesis predicts the onset of detectable MSD in a, less researched and highly loaded, circumferential butt joint at the crown of a RAF VC10 aircraft fuselage. The onset of detectable cracking is determined using a theoretical Monte-Carlo probabilistic simulation, which incorporates the results of extended fatigue specimen testing, to failure, of retired RAF VC10 fuselage structure using stresses derived from an in-service stress spectrum of the Joint. A biaxial fatigue analysis of the longitudinal bending and circumferential hoop stresses at the Joint, identifies that the large longitudinal stress from this rear engine large T-tail aircraft are dominant in determining the fatigue endurance of the Joint. Fracture surface analysis, however, identifies that the applied test load is different to the stress state experienced in the fuselage. A possible cause for the discrepancy is identified as secondary bending due to the asymmetry of the butt joint and the unrestricted out-of-plane displacement of the specimens during testing. All the specimens exhibited small (50x1 O'6 m) pre-existing cracks and corrosion pits which, in comparison to ‘similar’ pristine specimens, suggests (not substantiated) that environmental and operational degradation contributes to reducing airframe joint rivet hole fatigue endurance and standard deviation.